Gravity & Grace : The changing condition of Sculpture 1965-1975. - Ferleger Brades, Susan; Meyric Hughes, Henry; Safran, Yehuda; Thompson, Jon; Tucker, William; Hayward Gallery, London (London : South Bank Centre, 1993)
Anselmo, Giovanni ; Beuys, Joseph ; Broodthaers, Marcel ; Fabro, Luciano ; Flanagan, Barry ; Hesse, Eva ; Kounellis, Jannis ; Long, Richard ; Merz, Mario ; Morris, Robert ; Nauman, Bruce ; Panamarenko ; Paolini, Giulio ; Penone, Giuseppe ; Pistoletto, Michelangelo ; Ruthenbeck, Reiner ; Serra, Richard ; Smithson, Robert ; Sonnier, Keith ; Zorio, Gilberto
Engels
boek